DESCRIPTION OF CAREER WOMEN IN BONTOA VILLAGE, MAROS DISTRICT - Khusnul Yuliana, Asmirah; Afiif, Ahmad; Damayanti, Eka (JURNAL SIPAKALEBBI, 2023)
The first care for children lies within the family. The main responsibility of caring for childrenis still borne by the father or mother even though they have other activities outside the home,such as working. Caring for mothers or working women is interesting to study because of thedouble burden that is carried out apart from being a caregiver as well as an employee atwork. This article discusses caring for career women in the Bontoa Village. The data sourcesin this study were 5 housewives as well as career women who have children under the age of5 in Bontoa Village, Maros Regency. The research instrument uses an interview guide. Thedata analysis technique uses descriptive analysis through the stages of data reduction, datapresentation, and drawing conclusions. Research results show that: (1) The parenting modelapplied by career women in Bontoa Village, Maros Regency, namely democratic,authoritarian, and permissive parenting. Democratic parenting by considering the rules, notimposing the will of parents which can make children depressed. Authoritarian parentingwhere parents pressure children to do what parents want. Permissive parenting freeschildren in determining their desires. (2) Career women in the Bontoa Village, MarosRegency, in carrying out their roles as caregivers and also as career women have determinedpriority activities. Work problems can affect the home and children or vice versa. The mostimportant thing is to build effective communication with family so that they can actualizethemselves in their respective fields of work.